Pelatihan Problem Focused Coping untuk Mengurangi Prokrastinasi Akademik pada Mahasiswa - Rini Eka Sari; Andreas Yudha Fery Nugroho (LP2M Universitas Sarjanawiyata Tamansiswa, 2021)
This research is an experimental study which aims to determine the effectiveness of problem focused coping training in reducing academic procrastination in students. The subjects in this study were students of the Faculty of Psychology, Sarjanawiyata Tamansiswa University Yogyakarta. The measuring instrument used in the form of Academic Procrastination scale with a reliability coefficient value of 0.931. The collected data were analyzed by statistical analysis of different test. Hypothesis testing in this study used Paired sample t-test and independent sample t-test. The results of statistical analysis with different tests in the experimental group obtained the initial t number = 116.731 and the final t = 93,492 meaning that there was a significant influence between providing problem focused coping training for reduce academic procrastination in students. Pair1 test results obtained sig value. (2- tailed) of 0.000 where P <0.05, it can be concluded that there is a difference in the average academic procrastination of students for the pretest and posttest in the experimental group. And the pair2 test results obtained the sig value. (2-tailed) of 0.000 (P <0.05), it can be concluded that there is a difference in the average academic procrastination of students for the pretest and posttest in the control group.